Can smartphone-based diabetes control apps improve cardiovascular risk among patients with diabetes? A systematic review and meta-analysis - Refin, Randa Y.; Andika, Fina F.; Abudurrahman, Muhammad F.; Maidar, Maidar; Yufika, Amanda; Mulya, Intan C.; Parperis, Konstantinos; Abdeen, Ziad (Narra X, 2024)
Despite being the most prevalent complication, cardiovascular risk factors such as blood pressure, weight, and lipid profile have been less considered in digital health studies. The aim of this systematic review and meta-analysis was to gather evidence regarding the impact of digital health applications on cardiovascular risk factors in patients with diabetes. Literature search was conducted following the PRISMA guideline on September 4, 2023, using databases including PubMed, Scilit, Scopus, Embase, and Web of Science, with a pre-planned combination of keywords. Selected studies were original research reporting the influence of smartphone applications on cardiovascular risk factors in diabetic patients. Standardized mean differences (SMD) between the intervention and control groups were analyzed using fixed or random-effects models. Eighteen studies met the criteria, consisting of 1152 patients in the intervention group and 1072 patients in the control group. The results of the meta-analysis showed that the smartphone applications significantly controlled systolic blood pressure (SMD: -5.03 mmHg; 95%CI: -7.018–(-3.041), p<0.001). There was no significance effect on weight, body mass index, total cholesterol, low-density lipoprotein cholesterol (LDL-c), high-density lipoprotein cholesterol (HDL-c) and diastolic blood pressure. In the subgroup analysis, triglycerides were lower in the intervention group compared to the control group (SMD: -0.459%; 95%CI: -0.787–(-0.132), p=0.006). Publication bias and the limited number of studies suggest that the evidence from this study is in moderate level. In conclusion, smartphone apps are not only effective in aiding blood sugar control but also in preventing cardiovascular issues in diabetic patients. Further research is still needed to confirm these findings.